2016
DOI: 10.4103/0974-8490.171100
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofBeta vulgarisLinn. leaves extract on anxiety- and depressive-like behavior and oxidative stress in mice after acute restraint stress

Abstract: Background:Stress plays a significant role in the pathogenesis of neuropsychiatric disorders such as anxiety and depression. Beta vulgaris is commonly known as “beet root” possessing antioxidant, anticancer, hepatoprotective, nephroprotective, wound healing, and anti-inflammatory properties.Objective:To study the protective effect of Beta vulgaris Linn. ethanolic extract (BVEE) of leaves against acute restraint stress (ARS)-induced anxiety- and depressive-like behavior and oxidative stress in mice.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 30 publications
7
34
0
Order By: Relevance
“…[23] Thus, to exclude motor stimulation activity of EECS, locomotor activity test was also performed. Our results are consistent with other studies[923] indicating that EECS at same doses that produce antidepressant-like activity, did not show motor stimulation. Since decreased immobility time was not accompanied by hyperlocomotion (that could produce false positive results) specific antidepressant-like activity of EECS can be confirmed from the above results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…[23] Thus, to exclude motor stimulation activity of EECS, locomotor activity test was also performed. Our results are consistent with other studies[923] indicating that EECS at same doses that produce antidepressant-like activity, did not show motor stimulation. Since decreased immobility time was not accompanied by hyperlocomotion (that could produce false positive results) specific antidepressant-like activity of EECS can be confirmed from the above results.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, ARS significantly increased the duration of immobility in FST and TST, indicating depressive-like behavior as demonstrated in earlier studies. [4921] Pretreatment with EECS for 7 days, provided significant protection against ARS induced increased immobility time in FST and TST which supported the findings obtained in similar studies on evaluation of antidepressant-like effect. [49]…”
Section: Discussionsupporting
confidence: 80%
“…Earlier it has been reported that leaves of beetroot have shown to possess significant antioxidant property [9][10]. Therefore, the present study was aimed to evaluate the antioxidant property of beetroot that is consumed as a vegetable in various parts of the world including India.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also shown, leaves of Beta vulgaris possess strong anti-oxidant properties [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves are a good source of natural antioxidant and widely consumed as vegetables due to its high nutritional value. 6 Epidemiological studies have suggested positive associations between the consumption of phenolic-rich foods or beverages and the prevention of diseases. These effects have been attributed to antioxidant components such as plant phenolics, flavonoids and phenylpropanoids among others.…”
Section: Introductionmentioning
confidence: 99%